Internal transcribed spacer sequence-based rapid molecular identification of Prototheca zopfii and Prototheca blaschkeae directly from milk of infected cows - Marques, Sara; Huß, Volker; Pfisterer, K.; Grosse, C.; Thompson, G. (Journal of Dairy Science, 2015)
The increasing incidence of rare mastitis-causing pathogens has urged the implementation of fast and efficient diagnostic and control measures. Prototheca algae are known to be associated with diseases in humans and animals. In the latter, the most prevalent form of protothecosis is bovine mastitis with Prototheca zopfii and Prototheca blaschkeae representing the most common pathogenic species. These nonphotosynthetic and colorless green algae are ubiquitous in different environments and are widely resistant against harmful conditions and antimicrobials. Hence, the association of Prototheca with bovine mastitis represents a herd problem, requiring fast and easy identification of the infectious agent. The purpose of this study was to develop a reliable and rapid method, based on the internal transcribed spacer (ITS) sequences of ribosomal DNA, for molecular identification and discrimination between P. zopfii and P. blaschkeae in bovine mastitic milk. The complete ITS sequences of 32 Prototheca isolates showed substantial interspecies but moderate intraspecies variability facilitating the design of species-specific PCR amplification primers. The species-specific PCR was successfully applied to the identification of P. zopfii and P. blaschkeae directly from milk samples. The intraspecific ITS phylogeny was compared for each species with the geographical distribution of the respective Prototheca isolates, but no significant correlation was found.
Keywords: Prototheca spp. bovine mastitis; internal transcribed spacer (ITS); rapid molecular identification; species-specific PCR (ssPCR); geographical distribution